An example of the adverse impacts of various anthropogenic activities on aquatic bodies: Water quality assessment of the Provadiyska River (Northeastern Bulgaria) - Seymenov, Kalin (Geographica Pannonica, 2022)
Anthropogenic activities deteriorate the quality of water resources, which reduces their socio-economic suitability, endangers public health, and affects aquatic life. This work presents the results of physicochemical monitoring of the Provadiyska River (Northeastern Bulgaria) and aims to assess water quality status according to the guidelines pointed out in the National regulatory standard – Regulation H-4/2012 for characterization of the surface waters. The selected river has become one of the most seriously polluted streams in the territory of the country due to the effect of various human practices occurring in the drainage basin, such as agriculture, industry, and urban development. Data about the values of ten physicochemical variables (pH, EC, DO2, N-NH4, N-NO3, N-NO2, N-tot, P-PO4, P-tot, and BOD5), recorded at four measuring points during the period 2015–2020 have been used. Results obtained indicate that almost all of the parameters considered do not meet the reference norm for “Good status”, thus water quality could be assessed as “Moderate”. Failed variables appear to be EC, N-NH4, N-NO3, N-NO2, N-tot, P-PO4, P-tot, and BOD5 whose highest observed content remains from two up to nine times above the maximum permissible limits of Regulation H-4/2012. Water contamination arises from different sources and activities, including the excessive fertilization of croplands, the unregulated release of animal manure from livestock farms, the uncontrolled discharge of municipal and industrial effluents into the river, etc. The expansion of sewerage systems in the settlements, the construction of wastewater treatment facilities, as well as the adoption of codes for best farming practices are among the most important actions that should be taken to reduce the deleterious effects of various anthropogenic activities on water quality.